Technological, Media, and Pedagogical Developments: Digital Transformation in the Era of Education 4.0 and 5.0 - Ni Nyoman Ayu Pradnyawati Pradnyawati (APS-TPI, 2026)
Background: The rapid development of information and communication technology (ICT) has fundamentally transformed the learning process in education. Digital integration enables learning to be flexible, interactive, and student-centered, aligning with the demands of 21st-century skills. This transformation has been further accelerated by the COVID-19 pandemic, which encouraged the widespread adoption of online learning, digital media, and innovative learning methods. However, the implementation of educational technology still faces various challenges related to human resources and infrastructure readiness.Aims: This study aims to comprehensively examine the recent development of learning technologies, learning media, and instructional methods, as well as their implications for the quality of the learning process within formal education contexts.Methods: The research employed a library research design using a qualitative descriptive approach. Data were collected from national accredited journals and reputable international journals published within the last 10–15 years. The data were analyzed using qualitative content analysis to identify patterns, trends, and key findings related to technology, media, and learning methods.Result: The results indicate an increasing use of Learning Management Systems (LMS), artificial intelligence, and virtual and augmented reality technologies to support flexible and personalized learning. Learning media have shifted toward interactive digital formats that enhance student motivation and engagement. Innovative instructional methods such as blended learning, flipped classroom, project-based learning, and problem-based learning are increasingly implemented to promote active and collaborative learning, although challenges related to access inequality and digital literacy persist.Conclusion: The integration of technology, learning media, and innovative instructional methods plays a crucial role in educational transformation. Effective implementation requires adequate pedagogical readiness, digital competence, and equitable infrastructure support to ensure meaningful and high-quality learning outcomes.